The Eeffectiveness of YouTube Used as a Media for Teaching Eight Grade Students of 268 Jakarta Junior High School English Listening Skills - Almira Afiah Azaria; Burhayani Burhayani (Linguistic, English Education and Art (LEEA) Journal, 2024)
This research aims to investigate the efficacy of incorporating movies into English language instruction specifically to improve the listening skills of students at 268 Jakarta Junior High School. Jakarta, being a vibrant cosmopolitan hub, presents a diverse linguistic landscape where English proficiency holds significant relevance for academic, professional, and social advancement. The study aims to provide statistically significant insights into the effectiveness of this innovative teaching method. The study will adopt a quasi-experimental design with a non-equivalent control group. The findings of this research lead to the conclusive understanding that the utilization of films as English language learning media proves to be effective in enhancing the listening skills of students at SMPN 268 Jakarta. Keywords : Listening Skills, Media, Teaching